PERAN ORANG TUA DALAM MEMBANGKITKAN SEMANGAT BELAJAR ANAK USIA SEKOLAH DASAR PASCA PENDEMI COVID 19 DI KOTA PADANG - Handayani, Revi; Wiwita, Risma; Mayeni, Riska; Ramadhani, Ramadhani (STKIP Pesisir Selatan, 2022)
This study describes the post-covid-19 situation and the readiness of elementary school children to conduct face-to-face learning. This qualitative descriptive research method is used to analyze events, phenomena, or social realities. Data obtained from various sources, data collection techniques through instruments carried out by researchers, such as observation, interviews and documentation. The research subjects are informants, namely people who provide an overview of the current situation, namely the social situation or social situation which consists of three elements, namely place (palce), actors (actors), and activities (activity) that interact synergistically. Then the analysis and conclusion, the location of this research in the city of Padang. This study sees that in re-implementing post-online learning during covid 19, the role of parents must be fully carried out to revive children's enthusiasm because they are accustomed to learning using technology such as gadgets. The city of Padang currently has a full face-to-face meeting with elementary school-aged students who are asked to return to their normal classes before COVID-19 hit. This is certainly not easy to change because it has long been complacent because at this age children need an active role from parents as their guides in getting to know learning again. Judging from the results of this study, post-covid-19 learning can be carried out properly if there is full guidance for children, and the readiness of parents is very meaningful.